$(\sim q \wedge (p \rightarrow q)) \rightarrow \sim p$
We know that $p \rightarrow q \equiv \sim p\vee q$
$(\sim q \wedge (\sim p\vee q)) \rightarrow \sim p$
Convert $\wedge\equiv\cdot ,\vee\equiv +$
Now, $\overline{q}.(\overline{p}+q)\rightarrow \overline{p}$
$(\overline{q}.\overline{p}+\overline{q}.q)\rightarrow \overline{p}$
$(\overline{p}\cdot\overline{q}+0)\rightarrow \overline{p}$
$\overline{p}\cdot\overline{q}\rightarrow \overline{p}$
$\overline{\overline{p}\cdot\overline{q}}+\overline{p}$
$p+q+\overline{p}=p+\overline{p}+q=1+q=1$
Now we can write $p \vee \sim p\equiv \sim q\vee p\equiv T$
So, this is Tautology.